Health status as a mediator variable in the case of factors affecting foreign investment in the KSA - Nasrulddin, Vivian Mohammad; Alsulami, Salwa Murayziq (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to analyze the role of health status as a mediating variable in the relationship between a set of economic factors (such as the number of factories, patent registrations, financial development, government infrastructure expenditure, and gross fixed capital formation) and foreign direct investment (FDI) in the Kingdom of Saudi Arabia during the period 2005–2024. The study adopted a descriptive analytical approach and used the mediating regression model to examine the nature and extent of relationships among the variables.Data were analyzed using the Statistical Package for the Social Sciences (SPSS) through the Process Macro tool. Direct and indirect effects were tested using the Bootstrap technique, based on annual data obtained from official sources. The validity and reliability of the study instruments were verified using Cronbach’s alpha coefficient, which reached (0.829), indicating a high level of internal consistency.The results revealed statistically significant direct effects between economic factors and health status, as well as a significant effect of health status on FDI. However, most of the indirect effects through health status were not statistically significant. The indirect effect of some variables reached (0.41), indicating a moderate effect size from a practical standpoint.The study recommended integrating health indicators into economic policies and enhancing the health environment as one of the key components for attracting foreign investment in the Kingdom.
Keywords: Foreign Direct Investment; Health Status; Patent Registrations; Financial Development; Government Expenditure; Life Expectancy